Enhancing (31)P NMR Relaxation Rates with a Kinetically Inert Gadolinium Complex - Tear, Louise R. (Dalton Trans, 2020)
The kinetically stable heptadentate gadolinium complex Gd.pDO3A (1.Gd) demonstrates significant (31)P nuclear magnetic resonance (NMR) relaxation enhancement of biologically relevant phosphate species; adenosine triphosphate (ATP), phosphocreatine (PCr) and inorganic phosphate (PO4(-)). Gd.pDO3A (1.Gd) binds these species in fast exchange, enabling the relaxation of the bulk phosphate species in solution. This gives rise to (31)P relaxation enhancements up to 250-fold higher than those observed for (31)P relaxation enhancements with the commercial MRI contrast agent Gd.DOTA (DOTAREM), 2. Gd.pDO3A-like complexes may have potential applications as (31)P magnetic resonance contrast agents, since shortening the T(1) relaxation time of phosphate species would reduce the time needed to acquire (31)P-MR spectra.